A review of medicinal plants and daily foods used in Southeast Asia possessing antidiabetic activity - Wan Nadilah Adibah, W. Ahmad; Nor Hasima, Mahmod; Abd Manaf, Ali (2019)
According to the recent estimates by the World Health Organization (WHO), 422 million adults aged over 18 years were living with diabetes in 2014 globally. Surprising, about 1.6 million deaths was reported cause directed by diabetes in 2016. In Southeast Asia alone, 96 million people have diabetes, and this is predicted to increase. The incidence of diabetes is worryingly increasing especially in developing countries. Numerous synthetic drugs have been discovered to control this disease, but these drugs can lead to negative side effects. Therefore, people are looking for natural remedies to combat the disease. The objective of this review is to study of the medicinal plants and daily foods that have been used to treat diabetes. Instead of common traditional medicinal plants such as Andrographis paniculata, Averrhoa bilimbi, Camellia sinensis, Cosmos caudatus Kunth, Leucaena leucocephala, Momordica charantia, Ocimum sanctum, Orthosiphon stamineus, Panax ginseng and Pereskia bleo and; daily foods ingredients like fenugreek, garlic, ginger, onion and turmeric possess significant positive effects on diabetic patients. Antioxidants, for instance andrographolide, flavonoids glycosides like epicatechin, quercetin, catechin, myricetin, epigallocatechin gallate, polysaccharide compound galactomannan, saponin, gingerol, allicin, euganol and curcuma, dietary fibers and some minerals such as magnesium as well as amino acid such as 4- hydroxyisoleucine were found to be responsible for this effect. Although some responsible compounds are known, the mechanisms involved are not yet fully explored. Thus, further research on the mechanism, effective dosage and toxicity of the particular medicinal plants need to be comprehensively studied before they can be marketed as nutraceutical products.